Consumer myopia: a gap analysis between attitude and sustainable behavior - Paiva, Marlon Bruno Matos; Oliveira, Lais Vieira Castro; Romero, Cláudia Buhamra Abreu; Guimarães, Daniel Barboza (Revista de Administração da UFSM, 2017)
The aim of this research was analyzing attitude and behavior of the public workers of a Federal University, in relation to sustainability issues, through a case study at Federal University of Ceará (UFC). In order to achieve this, in a sample of 298 workers from UFC, we analyzed the variables attitude, behavior at workplace and outside the workplace, as well as a possible gap among these variables, conducted by descriptive and factorial analysis, and Pearson’s correlation. The results showed that there is green marketing myopia in attitudes and behavior of the individuals, but the level of myopia was considered low at all scales. While paper consumption was the item with greater impact on behavior at work, outside the workplace, disposal of waste showed greater influence on behavior. Also it was found that attitude is positively correlated to environmental behavior, both inside and outside the workplace with moderate effect, and between those two types of behavior, there is correlation with strong effect. Furthermore, it was noticed that correlation between attitude and environmental behavior is stronger among professors, and between federal workers with higher education.